2016
DOI: 10.1056/nejmc1603274
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in Multidrug-Resistant Tuberculosis

Abstract: W e read with great interest the mathematical model presented by Fofana et al. (1) on the role of pyrazinamide (PZA) in the emergence of multidrug-resistant tuberculosis (MDR TB), particularly as the results of their model mirror our concerns regarding the amplification of PZA resistance during inappropriate first-line therapy and the dramatic negative consequences that this can have on the subsequent response to second-line therapy. Indeed recent data from Belarus suggest that approximately 50% of PZA resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
85
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 3 publications
(2 reference statements)
5
85
0
2
Order By: Relevance
“…300 In 2016, analysis of European data also showed that 6-month culture conversion had high sensitivity for predicting disease-free relapse. 301 Thus, late culture conversion is associated with poor outcomes. 302,303 However, a time-specific cutpoint is dependent on the effectiveness and sterilising activity of the regimen used.…”
Section: Monitoring Treatment Response and Predicting Outcomementioning
confidence: 99%
“…300 In 2016, analysis of European data also showed that 6-month culture conversion had high sensitivity for predicting disease-free relapse. 301 Thus, late culture conversion is associated with poor outcomes. 302,303 However, a time-specific cutpoint is dependent on the effectiveness and sterilising activity of the regimen used.…”
Section: Monitoring Treatment Response and Predicting Outcomementioning
confidence: 99%
“…Fifty‐seven percent of patients with ‘treatment failure’ were not identified by the WHO definition because they did not change two drugs in the treatment regimen despite fulfilling criteria of failure . Recently, simplified treatment outcome definitions for MDR‐TB have been proposed (Table ) that are based on the culture status at the sixth month and include an observation period of 1 year after the end of therapy to define relapse‐free cure (while WHO outcomes are censored on the last day of treatment). Applying these definitions to patients with M/XDR‐TB leads to more accurate and plausible results with relapse‐free cure rates in M/XDR‐TB that are indistinguishable from those in non‐M/XDR‐TB under optimal management conditions …”
Section: Redefining Treatment Outcomesmentioning
confidence: 99%
“…MDR-TB treatment outcome definitions according to WHO 201491 and TBNET 2016 (simplified definitions)92 …”
mentioning
confidence: 99%
“…2 Despite this, Günther et al question the need for even 3 cultures to define successful treatment outcomes. 3 Although sending mycobacterial cultures can be onerous and expensive, it pales in comparison to the actual costs of MDR-TB treatment (range: US$10,000–200,000 versus culture: US$1.63–62.01). 4,5 The authors note that 11% of their participants who had culture-converted by 6 months later relapsed.…”
mentioning
confidence: 99%